The Competition “Recensiamo ItaliAMO” – About Rivalry that Encourages to Study Language and Explore Literature - Groblińska, Justyna; Kowalik, Katarzyna (Ludicity in (Glotto)Didactic, 2020)
The observations of creative forms of teaching foreign languages and literature included in this article are based on experiences gained thanks to organization of two editions of competition “Recensiamo ItaliAMO” at University of Łódź in 2018 and 2019. The competition invites students to create reviews of Italian literary works published after 2000. The first part presents didactic motivations that led us to propose such a form of optional activities to students and a description of the competition rules. The following analysis of the collected material allows to find out about students’ literary choices and to estimate their positive role in the didactic process and broadening of cultural skills. It provides also a possibility to observe such a negative phenomenon as neophilological students’ difficulties with composing a linguistically correct text or lack of capacity to use the book review’s genre rules. All these aspects provide precious knowledge that can be employed later in didactic work to plan lessons of practical language and literature.